FLOATING MICROSPHERES AS NOVEL DRUG DELIVERY SYSTEM FOR ARTHRITIS - Varghese, Rinu; Nair, Nikhila M.; L., Lekshmi; R., Anitha Lekshmi M.; Nair, Mohana M.; Abraham, Linku; Aniyan, Neema; A., Shajan (Asian Journal of Pharmaceutical Research and Development, 2016)
The aim of this review work is to investigate the efficacy of floating microspheres as novel drug delivery system in arthritis. Drug delivery is defined as the process of administering the drug or pharmaceutical product to achieve desired therapeutic effect. Drug delivery has a significant effect on therapeutic efficacy. Novel drug delivery system has a major advance to solve the problems related to the drug release at specific site. There are various approaches for delivering the drug to the site. One such approach of novel drug delivery system is floating microspheres. The slow efficacy in the treatment of rheumatoid arthritis and osteoarthritis has suggested the growing need of floating microspheres as novel drug delivery system in arthritis. Rheumatoid arthritis is a chronic autoimmune disease characterized by inflammation of the lining or synovium. Rheumatoid arthritis affect 1% of the adult Indian population. Osteoarthritis is a common degenerative disorder of the articular cartilage along with hypertrophic bone changes. Risk factors of osteoarthritis are past trauma, genetics, obesity, and advancing age .All possible areas of floating microspheres is enlighted in this review work. Floating microspheres are in strict sense, spherical empty particles without core, free flowing powders consisting of proteins or synthetic polymers with a size in the range 1-1000 micrometer. This review work gives brief information about rheumatoid arthritis, osteoarthritis, floating microspheres, method of preparations and application of floating microspheres in drug delivery.